2014
DOI: 10.5897/ajb2013.13493
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Nigerian brinjal eggplant (Solanum melongena L.) as revealed by random amplified polymorphic DNA (RAPD) markers

Abstract: The taxonomy of Solanum melongena L., also known as brinjal eggplant, has remained difficult because previous studies to establish genetic relationships among taxa are mainly based on morphological features, which are insufficient to establish genetic affinities. In the present investigation, five highly polymorphic random amplified polymorphic DNA primers were used to describe the genetic similarity and diversity among its accessions in Nigeria. The results show a high level of polymorphism based on the bandi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Based on dendrogram (Figure 3) we knew that also clustering wasn't in accordance with the collection area of eggplant, it can be seen in cluster B that accession from Sulawesi (K93) and NTB (K82) joined with accessions from Java, Sumatra, and Kalimantan. Some similar result ware also found in Mao et al (2006) were analyzing genetic diversity of Southern Chinese long-eggplant cultivars using ISSR markers the result is 57 eggplant cultivars divided into 6 groups that had no connection with regions of cultivars origin, Sifau et al (2014) analyzing genetic variation using the RAPD marker also states that grouping is not related to the origin area of eggplant accession and study by Sari et al (2018) using RAPD markers show that edible canna (Canna indica L.) in Indonesia divided into cultivar group based on morphological characters and was not influenced by geographical origin. Caguiat and Hautea (2014) also analyzed genetic variation of eggplant using SSR markers, they found that eggplant formed 3 groups that not related to the origin area of eggplant namely wild eggplant groups, cultivar groups, and landraces groups.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Based on dendrogram (Figure 3) we knew that also clustering wasn't in accordance with the collection area of eggplant, it can be seen in cluster B that accession from Sulawesi (K93) and NTB (K82) joined with accessions from Java, Sumatra, and Kalimantan. Some similar result ware also found in Mao et al (2006) were analyzing genetic diversity of Southern Chinese long-eggplant cultivars using ISSR markers the result is 57 eggplant cultivars divided into 6 groups that had no connection with regions of cultivars origin, Sifau et al (2014) analyzing genetic variation using the RAPD marker also states that grouping is not related to the origin area of eggplant accession and study by Sari et al (2018) using RAPD markers show that edible canna (Canna indica L.) in Indonesia divided into cultivar group based on morphological characters and was not influenced by geographical origin. Caguiat and Hautea (2014) also analyzed genetic variation of eggplant using SSR markers, they found that eggplant formed 3 groups that not related to the origin area of eggplant namely wild eggplant groups, cultivar groups, and landraces groups.…”
Section: Discussionsupporting
confidence: 75%
“…A dendrogram constructed by UPGMA cluster analysis from the ISSR data showing genetic relationship among accessions with similarity coefficient ranging from 0.661-0.881 ( Figure 3). Sifau et al (2014) indicating a fairly wide and diverse genetic base with high-level polymorphism and similarity coefficient ranging from 0.74 to 0.94 of Nigerian eggplant using RAPD markers. Marsolais et al (1993) suggested that range of similarity coefficient 0.50 using RAPD may be implied the occurrence of interspecific hybrid, while range between 0.61-0.99 could suggest genetic similarity at the species level in Lilac.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of genetic polymorphism is an efficient tool for the utilization and conservation of plant genetic resources because morphological keys are effective only for a particular stage of life (Sifau et al, 2014). The medicinal plants such as ginger, ginseng, bamboo and moringa have been characterized using DNA barcoding loci (Cortese et al, 2010).…”
Section: Flower Morphologymentioning
confidence: 99%
“…The morphological traits are also affected by micro climatic conditions although samples were collected from the same province. Therefore molecular methods coupled with morphological analysis are preferred for proper germplasm characterization and conservation (Sifau et al, 2014). Morphological features are inadequate to establish a genetic relationship especially for the species like Solanum, which are capable of crossing with more distant species (Daunay et al, 1999).…”
mentioning
confidence: 99%